Introducing the Text and Content of the Letters of Borhan Dynasty - mahdieh asadi; hosein masjedi (متن شناسی ادب فارسی, 2015)
Nafayes al-Kalam va Arayes al-Aqlam treatise is one of the prose works of seventh century which has been written by Razi al-Din Khashaab –Ahmad bin Mahmoud Samarqandi- in 643 (A.H). According to the preface of this letter-like treatise, the author was the head of letter-writers in the very year and, obeying the command of Eftekhar Jahan (one of the leaders of Borhan dynasty), he composed this work in order to prevent the destruction of the remained works of this dynasty. This treatise is a collection of correspondences of Borhan dynasty which confirms the reappointment of their government, at least until this very year.